Morphological characterization of two species of Abelmoschus: Abelmoschus esculentus and Abelmoschus caillei - Omonhinmin, C.A.=700 1 Osawaru, E.
(Es, En, Fr)
ilus., 17 ref.
Keywords: HIBISCUS ESCULENTUS; ANATOMIA DE LA PLANTA; VARIACION GENETICA; COMPETENCIA BIOLOGICA; NIGERIA; ABELMOSCHUS